Determinants of safety performance in healthcare settings: A meta-analysis - Prihatiningsih, Septyani; Martiana, Tri; Widajati, Noeroel; Fajar, Jonny K. (Narra J, 2025)
Safety performance among healthcare workers is an important issue, and currently, the factors related to it remain unclear. The aim of this study was to identify the factors related to safety performance among the healthcare worker population. This meta-analysis study was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) standards. Data on the factors affecting safety performance in the healthcare population were collected from each article to determine pooled point estimates. Data heterogeneity was evaluated using the Q statistic. Numerical data were analyzed using the inverse variance test, and the Mantel-Haenszel test was used for categorical data analysis. Pooled point estimates were presented as mean difference (MD) or odds ratio (OR) along with a 95% confidence interval (95%CI). Fifty articles were included in this study. Our results showed that nurses had lower safety performance compared to other professions (OR: 0.66; 95%CI: 0.56–0.79; p-Egger: 0.3739; p-Heterogeneity <0.0001; p<0.0001). On the other hand, it was also identified that housekeepers were associated with better safety performance compared to other professions (OR: 1.90; 95%CI: 1.08–3.35; p-Egger: 0.1577; p-Heterogeneity: 0.0950; p=0.0220). Furthermore, our findings revealed that healthcare workers who had undergone work safety training had better safety performance compared to those who had not (OR: 1.40; 95%CI: 1.01–1.95; p-Egger: 0.6124; p-Heterogeneity <0.0001; p=0.0430). In conclusion, this study has identified the factors contributing to safety performance in the healthcare population. These findings can inform policymakers in developing regulatory improvements regarding safety performance in healthcare workers.